Identification and Development of Sports Talent Program: A Study Based on George Edwards’ Factors of Policy Implementation - Pakasi, Aileen Fedora; Subarsono, Agustinus; Amali, Zainudin; Wahyuni, Sri; Pudyastuti, Supeni; Ferdinandus, Moses E. (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
the most positive impact on the implementation of Permenpora No. 6 Year 2022’s program, Talent Identification and Development Program, which has been going on since 2023 in every province in Indonesia. This study gathers the perspective of the National Association of Physical Education Teachers (IGORNAS) in D.I. Yogyakarta and Central Java towards the implementation of this program in their respective regions. A mixed-method approach is used in this study. The population consisted of 70 IGORNAS members in D.I. Yogyakarta and Central Java, with 37 respondents participating in the survey (52.86% response rate). The author distributed a questionnaire, which was made using the Likert Scale. The qualitative method using Nvivo software was also used in analyzing open-ended questions to gather more perspectives and concerns from IGORNAS. The findings of this study reveal the satisfaction level of the physical education teachers towards each factor, pointing out which factor needed more attention in order to make the Talent Identification and Development program more effective and successful in the upcoming years.